2016
DOI: 10.1111/jocn.13091
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a strengths‐based perspective support group among Taiwanese women who left a violent intimate partner relationship

Abstract: This research highlights the importance of nurses not only focused on problems but also on the psychological strengths in practice of abused women survivors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Hope has also been well established as a factor associated with the process of resilience following exposure to adversities [49][50][51][52]. Notably, prior research showed that hope can be increased through different therapeutic approaches or interventions [53][54][55]. Thus, shedding light into the role of hope as a potential factor that promotes resilience, can add to our knowledge on how this construct may be considered to inform the design of interventions targeting depression during this pandemic.…”
Section: The Mediating Role Of Resilience and Hopementioning
confidence: 99%
“…Hope has also been well established as a factor associated with the process of resilience following exposure to adversities [49][50][51][52]. Notably, prior research showed that hope can be increased through different therapeutic approaches or interventions [53][54][55]. Thus, shedding light into the role of hope as a potential factor that promotes resilience, can add to our knowledge on how this construct may be considered to inform the design of interventions targeting depression during this pandemic.…”
Section: The Mediating Role Of Resilience and Hopementioning
confidence: 99%
“…Among quantitative studies (n=57), there were six (11%) descriptive studies and 44 correlational studies (77%) that used observational approaches, with the former mainly adopting descriptive statistics while the latter more focusing on describing the relationships. We identified quasi-experimental research from Taiwan but categorised them into mixed methods studies because they all involved qualitative data collection [65] , [66] , [67] . Seven (12%) randomised controlled trials (RCTs) as experimental studies identified were all from Hong Kong.…”
Section: Resultsmentioning
confidence: 99%
“…Mixed methods studies as complex study designs were adopted in Hong Kong [24 , 83 , 102 , 103] and Taiwan [65 , 66] , which had a descriptive, correlational, or quasi-experimental quantitative strand mixed with a qualitative strand in various ways. A recent study from Hong Kong evaluated the Dating Compassion, Assessment, reFerral, and Education (CAFE) Ambassador Programme, a primary prevention program aiming to enhance behavioral intentions of college students to help peers experiencing dating violence, with a quasi-experimental study and qualitative evaluation using focus groups [103] .…”
Section: Resultsmentioning
confidence: 99%
“…For example, multiple studies targeting older adults mentioned the reduced happiness and well-being associated with aging (e.g., Ho et al, 2014 ; Bartholomaeus et al, 2019 ). Interventions with low-income populations mostly aimed at promoting well-being outcomes and building strengths to prevent mental health symptomatology associated with economic and living conditions (e.g., Hou et al, 2016 ; Rew et al, 2016 ; Sundar et al, 2016 ). In the context of populations with a physical health condition, positive psychology interventions were mostly used to improve recovery outcomes, and reduce associated psychological distress through increased positive psychology states (e.g., Millstein et al, 2020 ; Amonoo et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%